FREQUENCY OF PERICARDIAL EFFUSION IN PATIENTS WITH FIRST MYOCARDIAL INFARCTION AND ITS EFFECTS ON IN-HOSPITAL MORBIDITY AND MORTALITY - Rehman, Hafiz -ur-; Khan, Sher Bahadar; Hadi, Abdul; Nawaz, Tariq; Shah, Syed Tahir; ullah, Hameed; Gul, Adnan Mahmood; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Pericardial effusion (PE) is not an uncommon finding in serial echocardiographic evaluation of patients with AMI, especially when infarction is anterior and extensive. The objective of this study was to determine the frequency of pericardial effusion after first myocardial infarction and its effects on in-hospital morbidity and mortality. Methods: This descriptive study was performed in the Department of Cardiology, PGMI, LRH Peshawar, from July 2007 to December 2007. Main outcome measure was frequency of pericardial effusion. Results: Out of 200 patients with first acute myocardial infarction (AMI), mean age was 56±18 (28-90 years). Majority of patients (31.5%) were in the age range of 51-60 years. Males were 65.5% and 34.5% were females. Pericardial effusion was found in 4.5% patients on day 0, in 12.5% patients on day 2 and in 15% patients on day 4. Left ventricular failure was documented in 19 (9.5%) patients without and 42 (21%) patients with pericardial effusion (p<0.05%). Cardiogenic shock was reported in 5 (2.5%) patients without and 16 (8%) in patients with pericardial effusion and mitral regurgitation was found in 3 (1.5%) patients in each group. Death was recorded in 1 (0.5%) patient without pericardial effusion and was 1.5% (n=3) in patients with pericardial effusion. Conclusions: Pericardial effusion was seen in one third of the patients with first acute myocardial infarction. In acute phase of myocardial infarction, the chances of development of pericardial effusion increases as the time passes. Left ventricular failure was the commonest in-hospital morbidity followed by cardiogenic shock and mitral regurgitation. In-hospital mortality was more in patients with pericardial effusion. Keywords: Myocardial infarction, pericardial effusion, complications, diagnosis, echocardiography